2004
DOI: 10.1021/es0494858
|View full text |Cite
|
Sign up to set email alerts
|

Levels and Toxicokinetic Behaviors of PCDD, PCDF, and Coplanar PCB Congeners in Common Cormorants from Lake Biwa, Japan

Abstract: Concentrations of polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), and coplanar polychlorinated biphenyls (Co-PCBs) were determined in the liver and pectoral muscle of common cormorants (Phalacrocorax carbo) collected from Lake Biwa, Japan. To clarify the toxicokinetic behaviors and potential toxicities of these chemicals, the present study addresses life-stage- and tissue-specific accumulation of the congeners. Total 2,3,7,8-tetrachlorodibenzo-p-dioxin toxic equivalents (TEQs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
58
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 26 publications
14
58
0
Order By: Relevance
“…An in vitro study using hepatic microsomes from rats pretreated with AhR agonists showed rapid metabolism of PCB77 and 2,3,7,8-T 4 CDF by CYP1A enzymes [36][37][38]. In addition, our recent studies indicated preferential metabolism of PCB77 and 2,3,7,8-T 4 CDF in wild animals [12][13][14][15][16]. None of the mono-ortho PCB congeners was correlated with CYP1A-like protein levels, implying a relatively low contribution of these congeners for CYP1A induction.…”
Section: Drcs In Pig Livers and Toxicological Significancementioning
confidence: 98%
See 1 more Smart Citation
“…An in vitro study using hepatic microsomes from rats pretreated with AhR agonists showed rapid metabolism of PCB77 and 2,3,7,8-T 4 CDF by CYP1A enzymes [36][37][38]. In addition, our recent studies indicated preferential metabolism of PCB77 and 2,3,7,8-T 4 CDF in wild animals [12][13][14][15][16]. None of the mono-ortho PCB congeners was correlated with CYP1A-like protein levels, implying a relatively low contribution of these congeners for CYP1A induction.…”
Section: Drcs In Pig Livers and Toxicological Significancementioning
confidence: 98%
“…A study using transgenic Cyp1a2 knockout mice demonstrated that CYP1A2 is responsible for hepatic sequestration of certain DRC congeners [11]. Our previous studies demonstrated that distribution ratios of certain DRCs between liver and other tissues increased with total 2,3,7,8-tetrachlorodibenzo-p-dioxin toxic equivalents (TEQs) or CYP1A level in Baikal seals [12], common cormorants [13,14], jungle crows [15], and raccoon dogs [16], suggesting that hepatic sequestration of DRCs is dependent on CYP1A induction and TEQ levels. Furthermore, the potential of hepatic sequestration of DRCs varied among such species.…”
Section: Introductionmentioning
confidence: 99%
“…Sequestration of DP isomers by hepatic proteins could be a cause for their disposition in the liver although this was not identified (Li et al, 2013b). Exposure to xenobiotic pollutants such as polychlorinated dibenzo-p-diosins, polychlorinated dibenzo-furans, and coplanar PCBs may induce hepatic binding proteins leading to hepatic sequestration of the compounds (Kubota et al, 2004).…”
Section: Dynamic Tissue Distribution and Isomer Compositionmentioning
confidence: 99%
“…Polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/ Fs) and polychlorinated biphenyls (PCBs), which are two classical groups of dioxin-like compounds, are known to be the most hazardous to ecological and human health, and thus caused worldwide concerns and extensive research (deBruyn et al, 2004;Kubota et al, 2004). To evaluate their potential risk to environmental matrixes, consensus toxic equivalency factor (TEF) values for PCDD/Fs and PCBs have been derived (Van den Berg et al, 1998).…”
Section: Introductionmentioning
confidence: 99%